Hearing things - Claassen, José (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2016)
William Carlos Williams wrote: "It isn't what the poet says that counts as a work of art, it's what he makes, with such intensity of purpose that it lives with an intrinsic movement of its own to verify its authenticity." I would like to think that my poems only borrow life from my pen, taking on an identity and music of their own with the help of some 'making' on my part. My poems embrace a continuum of human experience from the intrapersonal to the societal. Using imagistic and cinematic forms, they preserve the vitality of their sources, from the music of cityscapes, to the texture of emotions, to the narratives of particular characters.
Keywords: Uncatalogued